Kampen om den danske gård. Dansk bondegårdsforskning i 1800- og 1900-tallet - Henningsen, Peter (Historisk Tidsskrift, 2019)
Research in Danish Peasant Buildings in the 20th Century Ethnological research on peasant houses and farm buildings was a major discipline at the Danish National Museum during a great part of the 20th century. Ethnologists were not interested in the farm buildings as such, but studied them as a cultural element and a means to understand contexts and developments in Schleswig, the Danish–German border region. German and Danish peasants were believed to build their farms in quite different ways, and scholars expected the peasant buildings in the region would reveal the national character of the Schleswig peasantry during the ages. Alas, comprehensive research clearly showed that the nationalist suppositions did not match the source material, and it became clear to several researchers that the old assumptions had been biased by an evolutionist approach. As a consequence, some ethnologists turned to new ‘diffusionist’ thought. The diffusionists rejected the old evolutionist schedules and were much more interested in cultural diversity, and in mapping the diffusion of single cultural elements such as peasant farms. How did one type of farm building spread to an area that previously had totally different farm buildings? This new orientation caused conflicts as the two main researchers in the field, Axel Steensberg and Svend Jespersen, had quite different opinions. Steensberg remained a hardcore evolutionist, whereas Jespersen espoused diffusionist views and, over the years, proceeded to functionalism and structuralism. They became harsh opponents and their disagreements made their museum department a tough place to work. When Jespersen died in 1958 and Steensberg turned his attention to other matters the strife petered out, and so did the research into peasant buildings. From time to time, new generations of historians and ethnologists have tried to revive the field, without success. Today, research into the history of peasant farms has itself become history, and thus it is now possible to give an assessment of this very special line of historical research.